PENGARUH KARAKTERISTIK AUDIT COMMITTEE DAN BOARD OF COMMISSIONERS TERHADAP AUDIT REPORT LAG - VAMELA PURNAMA; HERY GUNAWAN (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This research was created to examine internal factors within a company that can influence audit report lag. The factors used in this research are: Audit Committee Size, Audit Committee Expertise, Audit Committee Diligence, Board Size, Board Independence, Board Diligence, and Profitability. In this research, the data population was taken from manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the period 2020 - 2022. The manufacturing companies used are included in the Consumer Cyclicals and Consumer Non-cyclicals sectors. This research uses a purposive sampling method with a total final sample selected of 182 companies and 546 data that meet the criteria that have been studied using multiple linear regression. The results of the research show that Audit Committee Size, Audit Committee Diligence have no influence on Audit Report Lag. However, on the other hand, the Audit Committee Expertise, Board Size, Board Independence, Board Diligence, and Profitability have an influence on Audit Report Lag.